Analisis Integrasi Pasca Akuisisi Pada PT Arrahmah Muhammadiyah Jawa Tengah: Pendekatan Struktur-Perilaku-Kinerja (SCP) - Reziana, Febita Gita; Muhajarah, Kurnia (Kamaya: Jurnal Ilmu Agama, 2025)
This study aims to analyze the post-acquisition integration of PT Arrahmah Muhammadiyah using the Structure–Conduct–Performance (SCP) approach. The acquisition represents an internal affiliation within the Muhammadiyah organization, marked by the transfer of authority and assets from the Kendal Regional Board of Muhammadiyah (PDM) to the Central Java Regional Board (PWM) as a strategic effort to expand market reach and strengthen umrah service operations. This research adopts a qualitative approach through a case study of PT Arrahmah. Data were analyzed thematically to understand the integration process after the acquisition. The findings show an increase in the number of umrah departure groups from one to 3–5 groups per month. However, this achievement does not yet align with the company's 29-branch network. These results indicate that, despite the growth in departures, the branch network has not been fully optimized. The continued use of conventional promotional strategies targeted primarily at the Muhammadiyah community is a limiting factor. Nevertheless, the acquisition succeeded in forming a broader market structure, supported by Muhammadiyah’s strong branding as one of Indonesia’s largest Islamic organizations. This study contributes to management practice, particularly in managing the integration of community-based organizations to better leverage network potential and brand strength.